A brief lexico-semantic study of French and Kiswahili - (:unkn) unknown (My University, 2015)
Languages are influenced and enriched by others all over the world. Today, there is hardly any " pure " language in the world, devoid of borrowed words from other languages. In this paper, we are going to examine the lexical influence of French to Kiswahili, spoken and taught in Kenya. This language is spoken in the whole country and is a compulsory subject in the country's primary and secondary schools. Kiswahili is very present in East Africa and parts of Central Africa: it is spoken in Kenya, Uganda, Tanzania, Burundi, Rwanda and the Democratic Republic of Congo (DRC). However, it is mainly in Tanzania and Kenya that the importance of Standard Kiswahili is highly emphasized. Arguably, Kiswahili could easily be considered as the lingua franca of East Africa. People from some Indian Ocean islands such as Comoros Island and Mayotte also use this language. As is the case with many languages all over the world, different dialects of Kiswahili are spoken. Among these are ki-mvita, ki-amu, ki-ngozi and ki-ngwana.
Keywords: African Research